THE ANALYSIS OF FLOUTING MAXIM PERFORMED BY THE MAIN CHARACTER OF â€œSTRAWâ€ MOVIE - Insan Utama Sinuraya (Smart Education, 2025)
Abstract: This research aims to identify the types of flouting maxim performed by the main character in the Straw movie and to determine the strategies employed by the main character in flouting maxim. The research was conducted using a descriptive qualitative design. The data of this research are twenty-three dialogues of Straw movie containing flouting of the maxim. The data were gathered through observation and dialogue scripting. In analysing the data, the researcher found that Janiyah, as the main character of the movie, flouted all types of maxim. The most flouting maxim used by Janiyah was the floating maxim of relation, and the least flouting maxim performed by Janiyah was the flouting maxim of quality. The strategies are categorized as providing limited information, giving excessive information, using hyperbole, being irrelevant, changing the topic, and being obscure. The amount of the strategy that was frequently used to flout maxims was obscure. Â Keywords: pragmatics, flouting maxims, strategies of flouting maximsÂ Absrak: Penelitian ini bertujuan untuk mengidentifikasi jenis-jenis pelanggaran maksim yang dilakukan oleh karakter utama dalam film Straw dan untuk menentukan strategi yang digunakan oleh karakter utama dalam pelanggaran maksim. Penelitian ini dilakukan dengan menggunakan desain kualitatif deskriptif. Data penelitian ini adalah dua puluh tiga dialog film Straw yang mengandung pelanggaran maksim. Data dikumpulkan melalui observasi dan penulisan naskah dialog. Dalam menganalisis data, peneliti menemukan bahwa Janiyah, sebagai karakter utama film tersebut, melanggar semua jenis maksim. Pelanggaran maksim yang paling sering digunakan oleh Janiyah adalah maksim mengambang hubungan, dan pelanggaran maksim yang paling sedikit dilakukan oleh Janiyah adalah pelanggaran maksim kualitas. Strategi-strategi tersebut dikategorikan sebagai memberikan informasi terbatas, memberikan informasi berlebihan, menggunakan hiperbola, tidak relevan, mengubah topik, dan tidak jelas. Jumlah strategi yang sering digunakan untuk melanggar maksim adalah tidak jelas.Â Kata Kunci: pragmatik, pelanggaran maksim, strategi pelanggaran maksim